MENGENALKAN HURUF HIJAIYAH PADA ANAK USIA DINI - daman, Damanhuri; Jamiluddin Yacub (LPPM STAI DARUSSALAM LAMPUNG, 2022)
Abstrak The introduction of hijaiyah letters through the iqro method by teachers in introducing hijaiyah letters to children aged 4-5 years in Raudhatul Atfal (RA) Darul Huda Mataram Baru, East Lampung. This research was conducted in the form of qualitative and descriptive research. The data collection tools are interview guides, a list of observation guidelines, documentation data, and field notes. The results showed that the application of the iqro' method in introducing hijaiyah letters to children aged 4-5 years in Raudhatul Atfal (RA) Darul Huda Mataram Baru, East Lampung was good. The application of the iqro' method by the teacher in introducing hijaiyah letters to children aged 4-5 years in Raudhatul Atfal (RA) Darul Huda Mataram Baru, East Lampung is that children one by one recite or read hijaiyah letters who are guided by the teacher using the Iqro book. In addition, the teacher also introduces hijaiyah letters by writing some hijaiyah letters on the blackboard